Environmental Control, Internal Auditor and Good University Governance - Sukirman (EDP Sciences, 2021)
The Environmental control is essential for the achievement of organizational goals. Environmental control includes a management system, human resources, and information system. Hence, this research aims to examine the effect of an internal auditor and environmental control on good university governance. In addition, this research examines the role of the internal auditor on environmental control. The research sample technique used convenience sampling with a total sample of 121 respondents. This study uses primary data. The hypothesis test uses WarpPLS 7. The results show that internal auditor and environmental control affect good university governance. Furthermore, this study proves that the internal auditor could play a significant role in encouraging environmental control to run well and achieve the institution’s goal. Therefore, all organizations should improve the effectiveness of internal auditors. Future research is expected to add moderating variables like organization commitment.